2015
DOI: 10.1093/jac/dkv031
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal clearance of colistin methanesulphonate and formed colistin in end-stage renal disease patients receiving intermittent haemodialysis: implications for dosing

Abstract: Due to the extensive removal of CMS by dialysis, HD should be conducted at the end of a dosing interval and a supplemental dose should be administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…The CMS volume of distribution was moderately increased in ICU-HD patients compared with that in ICU-85 patients (Table 2), but, surprisingly, total clearance in ICU-HD patients (typical value, 113 ml/min) was virtually the same as that in ICU-85 patients (typical value, 112 ml/min). This result suggests that CMS nonrenal clearance (CL NRCMS ) is increased by approximately 2-fold (from 43.7 ml/min to 113 ml/ min) in HD patients, which was not seen in previous studies (5,8). Accordingly, CMS concentrations versus time profiles in typical ICU-HD and ICU-85 patients are virtually superimposed (Fig.…”
Section: This Study Allowed Comparisons Between Cms and Colistin Pk Imentioning
confidence: 58%
See 3 more Smart Citations
“…The CMS volume of distribution was moderately increased in ICU-HD patients compared with that in ICU-85 patients (Table 2), but, surprisingly, total clearance in ICU-HD patients (typical value, 113 ml/min) was virtually the same as that in ICU-85 patients (typical value, 112 ml/min). This result suggests that CMS nonrenal clearance (CL NRCMS ) is increased by approximately 2-fold (from 43.7 ml/min to 113 ml/ min) in HD patients, which was not seen in previous studies (5,8). Accordingly, CMS concentrations versus time profiles in typical ICU-HD and ICU-85 patients are virtually superimposed (Fig.…”
Section: This Study Allowed Comparisons Between Cms and Colistin Pk Imentioning
confidence: 58%
“…Second, the effect of HD sessions on colistin plasma concentrations was assessed by simulating 4-h HD sessions with different values of CMS and colistin HD clearances reported in the literature, i.e., 94.8, 90, and 94.8 ml/min for CMS and 56.7, 137, and 66.5 ml/min for colistin, respectively (5,7,8). For this simulation, PK parameter values-except HD clearances-were fixed to estimates of the present analysis, and the dosage regimen consisted of repeated administrations of CMS at 1.5 MIU every 12 h (q12h) and a supplemental reloading dose of 1.5 MIU administered along with the scheduled 1.5-MIU dose just after the HD session.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients receiving intermittent RRT, it's suggested to give an additional dose of colistin methanesulfonate sodium after dialysis (77,88), but no standardized dose recommendations are currently available for these long-lasting modalities of intermittent RRT. For end-stage renal disease (ESRD) patients receiving intermittent hemodialysis (HD), evidence from 10 patients indicated that HD should be conducted at the end of a dosing interval and a supplemental dose should be administered (89). A report of 8 continuous ambulatory peritoneal dialysis (CAPD) patients suggested that CMS doses should not be increased during CAPD because clearance by CAPD was low for both CMS and formed colistin (90).…”
Section: Dosing Strategiesmentioning
confidence: 99%